PERAN KEPALA SEKOLAH SEBAGAI MANAJER DI SMA NEGERI 4 TALANG UBI - Rumiatun Avdila; Herman Seri; Rytha Petrossky (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: This research was conducted at SMA Negeri 4 Talang Ubi which is located in Talang Akar Village, Kec. Talang Ubi, Kab. Penukal Abab Lematang Ilir, South Sumatra, 31211. The research objective in this study was to determine the role of the principal as a manager at SMA Negeri 4 Talang Ubi. The subjects of this study were the principal and all teachers at SMA Negeri 4 Talang Ubi, the number of samples in this study amounted to 21 teachers, the method used in this study was qualitative research. Based on the results of this study, it can be concluded that the results of interviews and questionnaires. Principals as managers can make plans, manage teaching and learning processes and always evaluate based on findings and make decisions based on the results of meetings that have been agreed upon. This was also reinforced by the results of the questionnaire showing that the teacher's perception of the principal's role as a manager, with a percentage of 96.8%, that the role of the principal as a manager at SMA Negeri 4 Talang Ubi is included in the Very Good category. Suggestions for Schools in carrying out learning (RPP) Principals must be able to motivate teachers to foster a sense of belonging to the school so that the learning process at school and the results can achieve the goals of education. For teachers to be more active and be able to foster a sense of belonging to the school and have responsibility in helping with all matters relating to the school. For future researchers, it is hoped that this can become a reference regarding the role of the principal as a manager in the school.Key Words: Role of Principal, Manager Abstrak: Penelitian ini dilakukan di SMA Negeri 4 Talang Ubi yang beralamat di Desa Talang Akar Kec. Talang Ubi, Kab. Penukal Abab Lematang Ilir, Sumatera Selatan, 31211. Tujuan Penelitian dalam penelitian ini adalah untuk mengetahui peran kepala sekolah sebagai manajer di SMA Negeri 4 Talang Ubi. Subjek Penelitian ini adalah kepala sekolah dan seluruh guru yang ada di SMA Negeri 4 Talang Ubi, jumlah sampel dalam penelitian ini berjumlah 21 guru, metode yang digunakan dalam penelitian ini yaitu penelitian kualitatif. Berdasarkan hasil penelitian ini dapat disimpulkan bahwa hasil wawancara dan angket Kepala Sekolah Sebagai Manajer, bisa membuat perencanaan, mengatur proses belajar mengajar dan selalu melakukan evaluasi berdasarkan temuan-temuan dan mengambil keputusan berdasarkan hasil rapat yang telah disepakati. Hal tersebut juga diperkuat dengan hasil angket bahwasanya persepsi guru terhadap peran kepala sekolah sebagai manajer, dengan persentase sebesar 96,8%, Bahwa Peran Kepala Sekolah Sebagai manajer di SMA Negeri 4 Talang Ubi termasuk dalam kategori Sangat Baik. Saran Bagi Sekolah dalam melaksanakan pembelajaran (RPP) Kepala Sekolah harus bisa memotivasi guru-guru agar menumbuhkan rasa memiliki sekolah agar proses pembelajaran disekolah dan hasilnya dapat mencapai tujuan dari pendidikan. Bagi Guru agar menjadi lebih aktif dan bisa menumbuhkan rasa memiliki sekolah dan mempunyai tangung jawab dalam membantu segalah urusan yang berkaitan tentang sekolah. Bagi Peneliti selanjutnya diharapkan bisa menjadi acuan tentang peran kepala sekolah sebagai manajer di sekolah. Kata Kunci : Peran Kepala Sekolah, Manajer